Pengaruh Bauran Pemasaran terhadap Kepuasan Konsumen pada UD. Olsabara Sukses Sejahtera Sangatta - Muhamad Yazid Bustomi; Indah Novita Dewi (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
Marketing activities as a bridge for arriving a product from producers to consumers. In these activities there were factors that influence customer satisfaction for knowing the company's stratgies. The objectives of this research were (1) to find out the effect of marketing mix (7P) on consumer satisfaction, and (2) to analyze the effect of consumer satisfaction on consumer loyalty who shop at UD. Olsabara Sangatta. The sampling technique used was accidental sampling, namely accidental sampling by taking the case of Olsabara visitors who want to be interviewed and are willing to fill out a questionnaire. The data analysis method was used structural equation model (SEM) analysis with SmartPLS software to determine the factors of the marketing mix that affect consumer satisfaction, and the effect of consumer satisfaction on consumer loyalty. The results showed that among the marketing mix variables that affect consumer satisfaction were people and physical evidence variables, while variables marketing mix of the product, price, promotion, place, and process have no significant effect on consumer satisfaction. The variable of consumer satisfaction had a significant effect on consumer loyalty. These results indicate that the attributes used in the people and physical evidence variables in the marketing mix need to be maintained and improved.